If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 5 = 2x + 6 + -4 Reorder the terms: 5 + 3x = 2x + 6 + -4 Reorder the terms: 5 + 3x = 6 + -4 + 2x Combine like terms: 6 + -4 = 2 5 + 3x = 2 + 2x Solving 5 + 3x = 2 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 5 + 3x + -2x = 2 + 2x + -2x Combine like terms: 3x + -2x = 1x 5 + 1x = 2 + 2x + -2x Combine like terms: 2x + -2x = 0 5 + 1x = 2 + 0 5 + 1x = 2 Add '-5' to each side of the equation. 5 + -5 + 1x = 2 + -5 Combine like terms: 5 + -5 = 0 0 + 1x = 2 + -5 1x = 2 + -5 Combine like terms: 2 + -5 = -3 1x = -3 Divide each side by '1'. x = -3 Simplifying x = -3
| -0.12q^2+1.8q-6=0 | | 33x+180=15 | | h(t)=-16t^2+800(t)+125 | | 4(v+5)=-2(9v-2)+8v | | 4x-(6x-2)=32 | | 6x^8+2x^4-5x^3+x^2-1= | | -2(-5v+8)-3v=3(v-7)-5 | | (3x^3+10x+5)-(x^3-4x-6)= | | 3w-5+3(3w+3)=-4(w+1) | | -5u-13=-2(u-7) | | 4x^3-8=100 | | 3.2+x=7.45 | | 9(y-4)=3y-6 | | x^3-3x=21 | | (3x^3+10x+5)-(x^3+4x-6)= | | -2x-23=3(x+4) | | 4c^3-8=100 | | -6(U+2)=4u+38 | | -3v+5(v-2)=-20 | | 14=5(x+5)+6x | | 14=4(w-4)-7w | | -c(5)-23=-18 | | x+16=2x+4 | | x+16=2x+3 | | 48+3w+10w=100 | | (8x^2)+(3x^2-2)= | | -3q^2+30q-48=0 | | 3x-90=46 | | 2x+6=2(x-8)+10 | | 4x^2-9y^2-16x-18y=29 | | m+(-13)=(-18) | | 293=3x |